Union Catalogs at the Crossroad - Lass, Andrew; Quandt, Richard E. (Hamburg University Press, 2004)
The Andrew W. Mellon Foundation and the National Library of Estonia organized a Conference on Union Catalogs which took place in Tallinn, in the National Library of Estonia on October 17-19, 2002. The Conference presented and discussed analytical papers dealing with various aspects of designing and implementing union catalogs and shared cataloging systems as revealed through the experiences of Eastern European, Baltic and South African research libraries. Here you can find the texts of the conference papers and the list of contributors and participants.